2017
DOI: 10.1186/s12885-017-3256-y
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of H3K27me3 as an epigenetic marker in prostate cancer progression

Abstract: BackgroundH3K27me3 histone marks shape the inhibition of gene transcription. In prostate cancer, the deregulation of H3K27me3 marks might play a role in prostate tumor progression.MethodsWe investigated genome-wide H3K27me3 histone methylation profile using chromatin immunoprecipitation (ChIP) and 2X400K promoter microarrays to identify differentially-enriched regions in biopsy samples from prostate cancer patients. H3K27me3 marks were assessed in 34 prostate tumors: 11 with Gleason score > 7 (GS > 7), 10 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 33 publications
(33 reference statements)
2
60
1
Order By: Relevance
“…Local recurrence and distant metastasis are the major patterns of treatment failure in NPC. Most cancers are caused by accumulation of genomic or epigenetic alterations [ 19 24 ], and epigenetic alterations play an important role in the development of NPC [ 9 , 25 ]. Several studies have indicated that aberrantly methylated genes could serve as prognostic biomarkers for NPC [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local recurrence and distant metastasis are the major patterns of treatment failure in NPC. Most cancers are caused by accumulation of genomic or epigenetic alterations [ 19 24 ], and epigenetic alterations play an important role in the development of NPC [ 9 , 25 ]. Several studies have indicated that aberrantly methylated genes could serve as prognostic biomarkers for NPC [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research by Ngollo et al Showed that GRID2 interacts with H3K27me3 in prostate cancer and is signi cantly overexpressed. [30] The protein encoded by ATG4D belongs to the ATG4 mammalian family (four cysteine proteases, ATG4A4D class), which is closely related to autophagosome maturation and apoptosis pathways [31]. Gil et al's research shows that ATG4D can play a role as a tumor suppressor in the development of colorectal cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment failure in NPC is usually due to local recurrence and distant metastasis (24). Recent studies have reported that epigenetic alterations play an important role in the initiation and development of most cancers (25)(26)(27)(28), including NPC (10,29). Several studies have also reported that aberrantly methylated genes may serve as prognostic biomarkers (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%